2004
DOI: 10.1039/b313213g
|View full text |Cite
|
Sign up to set email alerts
|

[Ru(TAP)2(dppz)]2+: a DNA intercalating complex, which luminesces strongly in water and undergoes photo-induced proton-coupled electron transfer with guanosine-5′-monophosphate

Abstract: The lowest excited state of [Ru(TAP)2(dppz)]2+ (TAP = 1,4,5,8-tetraazaphenanthrene, dppz = dipyrido[3,2-a:2',3'-c]phenazine) 1 is strongly luminescent, even in water, and very oxidizing. Therefore it is able to oxidise not only guanosine-5'-monophosphate (GMP), as demonstrated by laser flash photolysis, but also guanine-containing polynucleotides such as calf thymus DNA and [poly(dG-dC)]2. The luminescence quenching was found to be faster in H2O than in D2O, as is the back reaction, indicating that both proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
166
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 167 publications
(186 citation statements)
references
References 53 publications
19
166
1
Order By: Relevance
“…This observation may be contrasted with studies on tethered intercalators, where it was found that the ET yield, though not necessarily the rate, was affected by distance 3b. This may suggest the involvement of different mechanisms in our case, such as proton‐coupled ET 7b,c. Our experiments are consistent with the reactive excited state being a triplet ML(TAP)CT species, although a role for triplet ππ* state, as suggested by recent computational studies4 (and experiments on related systems)15 cannot be excluded.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…This observation may be contrasted with studies on tethered intercalators, where it was found that the ET yield, though not necessarily the rate, was affected by distance 3b. This may suggest the involvement of different mechanisms in our case, such as proton‐coupled ET 7b,c. Our experiments are consistent with the reactive excited state being a triplet ML(TAP)CT species, although a role for triplet ππ* state, as suggested by recent computational studies4 (and experiments on related systems)15 cannot be excluded.…”
contrasting
confidence: 81%
“…However, it may be noted that this lifetime is shorter than that for the excited state of [Ru(TAP) 2 (dppz)] 2+ either unbound (1080 ns) or bound to a duplex that does not contain G (e.g. poly{dA‐dT} 2 ; τ =1580 ns) 7b. This implies that excited‐state quenching occurs, but with a much lower rate than in A .…”
mentioning
confidence: 99%
“…Rac-½RuðTAPÞ 2 ðdppzÞCl 2 was prepared by a modification of the literature method (40). The two enantiomers were successfully resolved by introducing an aqueous solution of rac-½RuðTAPÞ 2 ðdppzÞCl 2 onto a Sephadex C-25 column with 0.1 M (-)-O, O′-dibenzoyl-L-tartrate as the eluent at 2 mL∕ min flow rate recycled by a peristaltic pump (23).…”
Section: Methodsmentioning
confidence: 99%
“…For instance it is often possible to select a complex with an excited state having an appropriate redox potential or one which shows exquisite sensitivity to its environment. [10][11][12][13][14][15][16][17][18] These properties are particularly valuable for potential therapeutic and diagnostic applications involving the interaction of such complexes with nucleic acids or proteins. [19][20] For example, directed photooxidative damage of nucleic acids opens the possibility of designing a new class of selective antitumour drugs.…”
Section: Introductionmentioning
confidence: 99%